2019
DOI: 10.3934/publichealth.2019.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Associations between breastfeeding duration and overweight/obese among children aged 5–10: a focus on racial/ethnic disparities in California

Abstract: Research on the association between breastfeeding and childhood obesity and research on racial/ethnic differences in breastfeeding both show inconsistencies. The current study examines: 1) whether immigrant Hispanic women have higher rates of breastfeeding compared to non-Hispanic (three separate groups: African-American, Asian/Pacific Islander, and White) and U.S.-born Hispanic women; 2) whether children who were breastfed are less likely to be overweight/obese compared to children who were not breastfed; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…After excluding duplicates, 17,871 titles were examined, and after excluding those studies that were clearly irrelevant, 269 abstracts were reviewed, and 58 19–76 new studies were identified in the update of the systematic review (Figure 1). The meta‐analysis comprised 169 estimates on the association of breastfeeding with overweight or obesity, drawn from 159 studies including 58 that were published since our previous review (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicates, 17,871 titles were examined, and after excluding those studies that were clearly irrelevant, 269 abstracts were reviewed, and 58 19–76 new studies were identified in the update of the systematic review (Figure 1). The meta‐analysis comprised 169 estimates on the association of breastfeeding with overweight or obesity, drawn from 159 studies including 58 that were published since our previous review (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…This rate of EBF differs compared to Latinx countries; for example, it was reported that EBF in Mexico was 91% at three weeks of life, in Brazil 57.8% at two months old infants, and in Nicaragua was close to 100% at hospital discharge (Ávila-Ortiz et al, 2020; Machado et al, 2020; Nabower et al, 2020). Even though it is evident that the Latinx women participating in this study wanted to feed their babies with their breast milk, as shown by the mean score on the IFI scale (12 over a total of 16), most of them supplemented with formula when they were hospitalized, which jeopardizes exclusive BF and may produce overfeeding in Latinx babies increasing their risk of obesity (Cartagena et al, 2018; Horta et al, 2023; Vazquez & Cubbin, 2019). We found that 60% of mothers who supplemented with formula had no specific reported reason for supplementation in their medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Anne sütü, ani bebek ölüm sendromu ve diyabet gibi sorunlara karşı da koruyucudur. Yapılan çalışmalar anne sütünün, bebeğin patojenlere karşı immün sistem bağışıklığını arttırdığını (3), yenidoğan ölüm riskini azalttığını (4), çocukluk çağı obezitesi için koruyucu bir faktör olduğunu (5) ve annede over kanser riskini azalttığını ortaya koymaktadırlar (1).…”
unclassified